TAX, MARKETING, AFTER-SALES SERVICE, AND FINANCIAL PERFORMANCE: ROLES OF INNOVATION AND MANAGEMENT - Ivan Gumilar Sambas Putra; Andhi Sukma; Louie A. Divinagracia (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This study investigates the influence of tax management, marketing strategy, and after-sales service on the financial performance of automotive firms in Indonesia, with a particular emphasis on the mediating roles of managerial quality and product innovation. Utilizing a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 240 industry professionals through purposive sampling. The results reveal that after-sales service and product innovation significantly enhance financial performance directly and indirectly. Product innovation is consistent and strong mediators. It also translates upstream strategic initiatives into financial outcomes. In contrast, managerial quality acts as a selective mediator shows significant impact only in the pathway from after-sales service to performance. The findings contribute to the Dynamic Capabilities framework by highlighting product innovation as a strategic internal enabler. Practically, they suggest that firms must integrate innovation and after-sales feedback systems to sustain competitive advantage. Meanwhile, managerial quality improvements should be aligned with operational domains to maximize impact. Furthermore, this study recommends a more integrated approach to tax planning, marketing strategy, service delivery, and innovation. Future research may extend the model to other sectors or use longitudinal data to establish causal relationships.